MENINGKATKAN HASIL BELAJAR MUATAN PPKn MATERI PERSATUAN DAN KESATUAN TERHADAP KEHIDUPAN BERBANGSA DAN BERNEGARA MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA SISWA KELAS VI SDN 91 KENDARI SEMESTER 1 TAHUN PELAJARAN 2022/2023 - Irmayani Irmayani (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
The results of the previous test, namely the daily test test in class VI at SDN 91 Kendari, showed that student learning outcomes were not optimal, because there were still several students who did not meet the minimum completeness criteria. Of the 22 students, there were around 7 students whose learning outcomes were still low. Learning strategies that will be used in existing problems are taken to make appropriate improvements through creative and fun methods, namely the use of project based learning learning models. This study uses an action research model (action research). An action that is specifically observed continuously, seen for pluses and minuses, then controlled changes are made to the maximum effort in the most appropriate form of action. This is in accordance with what is done by researchers. The subject of this research was Class VI of SDN 91 Kendari, which consisted of 22 students. The results of the pre-cycle research obtained classical student learning outcomes of 31.81% in the "very low" category, in cycle I had a percentage of 81.81% in the high category, while in cycle II the percentage was classically 100% in the "very high" category. The results of the evaluation of the second cycle showed that classical learning mastery reached (100%) with an average final score of students reaching (84.85) previously in the pre-cycle it was known that classical learning mastery reached (31.81%) with an average final test score students reached (63.17) and in the first cycle classical learning mastery reached (81.81%) with an average final test score of students (74.17). The project based learning learning model can be applied to Unity and Unity material for the Life of the Nation and the State because it can solve problems so that activity and cooperation increase and can develop students' motivation in studying the material so that instructional goals where students as educational subjects can be realized in carrying out tasks and obligations as students besides that, the role of the teacher as a facilitator and at the same time a companion in the teaching and learning process can be realized. From this information it can be concluded that the project based learning learning model can be applied to Unity and Unity material for the Life of the Nation and State and can improve learning outcomes in class VI semester 1 SDN 91 Kendari Academic Year 2022/2023.